Larvae of proceratophrys melanopogon (amphibia: anura), with emphasis on internal oral morphology and comparisons with p. cururu and p. moratoi - Provete, Diogo B.; Melo, Lilian S. O. [UNESP]; Garey, Michel V. [UNESP]; Gomes, Felipe B. R.; Martins, Itamar A.; Rossa-Feres, Denise C. [UNESP] (Herpetologists League, 2013)
We provide novel data on the biology of Proceratophrys melanopogon and describe its larval external morphology and internal oral features on the basis of specimens from the Serra do Mar, southeastern Brazil. We also review the larval internal oral features of the genus, including descriptions and comparisons with P. cururu and P. moratoi. The external morphology of tadpoles of P. melanopogon is very similar to that of closely related species. The internal oral features are very conserved in this genus, with the majority of species having lingual papillae unusually bifurcated, four infralabial papillae, and a transverse ridge on the prenarial arena. Our results also provide data for phylogenetic studies on the genus Proceratophrys.
Keywords: Atlantic rainforest; Larval morphology; Natural history